Quirky Tails - Jennings, Paul (Penguin Group, 1995)
Quirky? You can say that again. Look at it. His mouth is so small there is only just enough room to poke in one pea at a time. He can't talk, he can't stick out his tongue & he can't eat. You'll be speechless
Keywords: Juvenile literature-Horror-Collection (Stories)Fiction